CD8+ T-cells mediate immunopathology in tick-borne encephalitis - Růzek, Daniel; Salát, Jirí; Palus, Martin; Gritsun, Tamara S; Gould, Ernest A; Dyková, Iva; Skallová, Anna; Jelínek, Jirí; Kopecký, Jan; Grubhoffer, Libor (Virology, 2009)
Epidemics of tick-borne encephalitis involving thousands of humans occur annually in the forested regions of Europe and Asia. Despite the importance of this disease, the underlying basis for the development of encephalitis remains undefined. Here, we prove the key role of CD8(+) T-cells in the immunopathology of tick-borne encephalitis, as demonstrated by prolonged survival of SCID or CD8(-/-) mice, following infection, when compared with immunocompetent mice or mice with adoptively transferred CD8(+) T-cells. The results imply that tick-borne encephalitis is an immunopathological disease and that the inflammatory reaction significantly contributes to the fatal outcome of the infection.
Keywords: Animals; myši SCID; virová nálož; druhová specificita; lidé; Mice; CD8-Positive T-Lymphocytes; Species Specificity; přežívající; viry klíšťové encefalitidy; Mice, Inbred BALB C; Mice, SCID; myši; Encephalitis Viruses, Tick-Borne; Humans; CD8-pozitivní T-lymfocyty; Viral Load; myši inbrední BALB C; Encephalitis, Tick-Borne; imunokompetence; Survivors; CD4-Positive T-Lymphocytes; zvířata; klíšťová encefalitida; Immunocompetence; Paralysis; paralýza; CD4-pozitivní T-lymfocyty